Religion and the technological future : an introduction to biohacking, artificial intelligence, and transhumanism /: an introduction to biohacking, artificial intelligence, and transhumanism. (2021) - Mercer, Calvin R; Trothen, Tracy J (Tracy Joan), 1963-
No abstract available